Effect of oral administration of propylene glycol during periparturient period on blood biochemical parameters and liver triacylglycerol accumulation in postparturient dairy cows (African Journal of Dairy Farming and Milk Production, 2016)
Effect of propylene glycol administered during the periparturient period on blood biochemical parameters and liver triacylglycerol accumulation was studied in 35 dairy cows. Sixteen control cows were drenched with 400 ml of water per day starting from 7 days before expected calving date to 7 days after calving, while 19 treated cows were drenched with 400 ml of propylene glycol. Body condition scores and milk yield were recorded. Blood samples were collected at 2 weeks prepartum and at 2 and 4 weeks postpartum. Liver samples were collected at 2 weeks prepartum and 4 weeks postpartum. Control cows tended to lose more body condition scores than did treated cows during the first 4 weeks of lactation. Milk yield did not differ between control and treated cows. Serum nonesterified fatty acids concentrations in control cows were significantly higher than the concentrations in treated cows at 2 and 4 weeks postpartum. Serum glucose, triacylglycerol and urea nitrogen concentrations did not differ between the two groups at all sampling periods. Liver triacylglycerol concentrations were similar between 2 groups at 2 weeks prepartum. The concentrations in both groups increased at 2 weeks postpartum, and were significantly higher in control cows than in treated cows. Propylene glycol had an advantage to reduce adipose tissue lipolysis postpartum; as a consequence, reducing liver triacylglycerol accumulation.